Modeling Zucchini squash irrigation requirements in the Syrian Akkar region using the FAO56 dual-Kc approach - Darouich, Hanaa (2021)
The coastal area of the Syrian Akkar region is particularly suitable for intensive vegetable production, and Zucchini squash (Curcubita pepo L.) is one of the most profitable crops grown there. Local agricultural policies have been especially concerned at improving irrigation water management in the region by rationalizing water and nutrient use, modernizing irrigation methods, and minimizing the associated environmental risks. The objective of this study was to compute the soil water balance in Zucchini squash plots irrigated with furrow and drip methods using the SIMDualKc model during four growing seasons (2012–2015). The furrow plots (treatment T0) represented the traditional irrigation practices in the study area while the drip plots (treatments T1 and T2) followed alternative irrigation schemes. The SIMDualKc model was able to simulate soil water contents measured in the field plots, returning root mean square error values lower than 0.002m3m−3 and modelling efficiencies ranging from 0.166 to 0.732. The basal (non-stressed) crop coefficients (Kcb) varied from 0.18 to 0.22, 0.85 to 0.98, and 0.56 to 0.71 during the initial, mid-season, and end-season stages, respectively, with the actual values (Kcb act) often matching the potential ones. The evaporation coefficients (Ke) varied according to irrigation schedules and methods during the early crop stages, but were minimized with full canopy development. Drip T1 presented always the highest water productivity (WP) indicators due to the higher frequency of irrigation events, with less water applied per event. In contrast, furrow T0 resulted in substantial percolation losses, which affected yields and WP. Hence, model results evidenced the benefits of precise irrigation for Zucchini squash production in the Syrian Akkar region, further enhancing the need for sustainable water management practices in local production systems